Celowość wprowadzania controllingu w małej firmi - Nowosielski, Stanisław (The Expediency of Introducing Controlling into Small Enterprise, 2006)
In the paper causes and obstacles of implementing Controlling into small enterprise are described. The main factors which evoke Controlling are presented. The grounds for establishing the expediency of introducing Controlling into small business are also described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 358-368